Combined toxic effects of fludioxonil and triadimefon on embryonic development of zebrafish (Danio rerio). (May 2020) - Wang, Yanhua; Xu, Chao; Wang, Dou; Weng, Hongbiao; Yang, Guiling; Guo, Dongmei; Yu, Ruixian; Wang, Xinquan; Wang, Qiang
Abstract: Pesticides scarcely exist as individual compounds in the water ecosystem, but rather as mixtures of multiple chemicals at relatively low concentrations. In this study, we aimed to explore the mixture toxic effects of fludioxonil (FLU) and triadimefon (TRI) on zebrafish ( Danio rerio ) by employing different toxicological endpoints. Results revealed that the 96-h LC50 values of FLU to D. rerio at multiple developmental stages ranged from 0.055 (0.039–0.086) to 0.61 (0.33–0.83) mg L −1, which were less than those of TRI ranging from 3.08 (1.84–5.96) to 9.75 (5.99–14.78) mg L −1 . Mixtures of FLU and TRI exerted synergistic effects on embryonic zebrafish. Activities of total superoxide dismutase (T-SOD) and catalase (CAT) were markedly altered in most of the individual and pesticide mixture treatments compared with the control. The expressions of 16 genes involved in oxidative stress, cellular apoptosis, immune system and endocrine system displayed that embryonic zebrafish were affected by the individual pesticides and their mixtures, and greater variations of four genes ( ERɑ, Tnf, IL and bax ) were found when exposed to pesticide mixtures compared with their individual compounds. Therefore, more studies on mixture toxicities among different pesticides should be taken as a priority when evaluating their ecological risk. Graphical abstract: Image 1 Highlights: Fludioxonil elicited higher toxicity than triadimefon to zebrafish. Mixtures of fludioxonil and triadimefon displayed synergistic response on zebrafish. Expressions of 4 genes exerted greater changes in mixtures compared with individuals. Mixture toxic effects should be incorporated into the risk assessment of pesticides. Abstract : Mixture toxicity and potential mechanism of fludioxonil and triadimefon to the zebrafish.